Determinants on the choice of insurance products among Malay Muslims in Malaysia - Shahira Abdul Jabar (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
Since Malaysia is considered as a hub for Islamic finance, many Islamic terms were introduced including Islamic insurance called Takaful. Takaful is derived from the Arabic word 'kafalah', which means to guarantee, looking after, to help and to take care of one's needs. Takaful is based on two concepts, which includes “ta'awun'(mutual assistance) and “tabarru”(voluntary contribution). Even though Malaysia is successful in the Islamic financial system, there is still low penetration of Takaful among Malay Muslims in this country. That is the reason why the writer embarked on this study. The objective of this study is to identify the determinant factors which contribute to the choice of insurance between Takaful and conventional insurance among Muslim in Malaysia. Not only that, this study also aims to further understand on the subject of Takaful. Questionnaire is used in this study in order to gain the information. Descriptive statistics used in order to explain the results. The results from descriptive analysis showed that majority of Malay Muslims in Malaysia have awareness and knowledge in Takaful however, it is still low. Meanwhile, price and religiosity are the factors that determine the choice of insurance among Malay Muslim in Malaysia.